Factors related to outcome of anterior cruciate ligament reconstruction rehabilitation in male: fear of re-injury, quality of life and patient education / Rohani Haron - Haron, Rohani (2016)
There have been very limited studies conducted on subjective outcome with regard to psychological factor, quality of life (QOL) and patient education after anterior cruciate ligament reconstruction (ACLR) rehabilitation among male involved in recreational activities. This study investigated fear of re-injury, QOL and patient education after ACLR rehabilitation. The purposes were (1) to determine the correlation between fear of re-injury and functional activity performance; (2) to determine the correlation between QOL, fear of re-injury and functional activity performance; (3) to identify the determinants of QOL concerning patients' background, fear of re-injury and functional activity performance; (4) to explore patients' experience in patient education by patientphysiotherapist face-to-face interaction on ACLR rehabilitation; and (5) to explore patients perception of patient education related to QOL after ACLR rehabilitation. A cross-sectional survey was conducted on 60 participants recruited by convenient sampling. They completed background information form, IKDC, KOOS and Lysholm, Tanpa Scale of Kinaesiophobia and ACL-QOL after 14 to 16 weeks of ACLR rehabilitation. Data were analysed by Pearson and Spearman correlation including multiple linear regression. For phenomenological design, interview guide was used to conduct interviews on 10 participants taken by purposive sampling. The transcriptions were analysed by thematic network analysis. In the multi-method design, quantitative and qualitative studies were performed concurrently. The TSK and KOOS-symptoms revealed a very weak correlation (r = -.155) and QOL with all variables had mainly positive with strong correlation (r = .490 to .717). Only TSK showed negative correlation. Multiple regression model was significant [F(l 1,48) = 27.5, p < .001] with the predictors explaining 59.5% of the variation in QOL. Only KOOS-pain and KOOS-sport/recreation were the significant contributors to QOL. The network on interpersonal interaction in face-to-face teaching and the holistic approach in QOL described the usefulness of patient education. Three significant contributions to physiotherapy practice are identified. To improve the proficiency of practice, the creation of a specific checklist is essential to assess physical and psychological profile with the potential to improve QOL after ACLR rehabilitation. Furthermore, head of physiotherpy department need to impose a regulation on physiotherapists to use a standadised reading materials to promote adherence to patient education on ACLR rehabilitation. Finally, the Holistic Rehabilitation Strategy (HRS) model is applicable to education and research in physiotherapy and sport-related injury management of ACLR. Future research include (1) a survey by using a larger sample size to compare QOL, functional performance and fear of re-injury between male and female (2) a focus group for patients' perception on patient education reading material developed from the present study and its inter-relation with empowerment in functional, psychological and social wellbeing; and (3) the development of a multi-component questionnaire to evaluate the HRS model. The reading material may enhance efficiency in rehabilitation time frame by motivating patients in self management of ACL rehabilitation. Additionally, the HRS model is applicable to the enhancement of physical and psychological outcome as well as the planning of ACLR rehabilitation protocol.